2021
DOI: 10.1111/cyt.13050
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic count of fine needle aspiration material of gastrointestinal stromal tumours of the stomach underestimates actual mitotic count

Abstract: Introduction A mitotic count is required for histological grading in resections of gastrointestinal stromal tumours (GISTs). However, no consensus on the utility of mitotic count in fine needle aspiration (FNA) GIST material currently exists. This study examines the relationship between mitotic counts of FNAs and subsequent resections of GISTs of the stomach. Materials and methods We identified 39 cases of GISTs of the stomach diagnosed via FNA at our institution between January 1, 2014, and December 31, 2019,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The 2021 WHO classification also recommends the reporting of nuclear grade in pathology reports of E‐DPM 10,12,23 . A limitation of applying this grading system to cytology specimens is that mitotic counts in cytology specimens are known to be unreliable 53 . In the current study, we found it difficult to assess mitoses in cytology specimens because mitoses were generally not preserved in aspirate smear slides, and in some cases low tumor cellularity limited our ability to provide accurate mitotic counts.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The 2021 WHO classification also recommends the reporting of nuclear grade in pathology reports of E‐DPM 10,12,23 . A limitation of applying this grading system to cytology specimens is that mitotic counts in cytology specimens are known to be unreliable 53 . In the current study, we found it difficult to assess mitoses in cytology specimens because mitoses were generally not preserved in aspirate smear slides, and in some cases low tumor cellularity limited our ability to provide accurate mitotic counts.…”
Section: Discussionmentioning
confidence: 71%
“…10,12,23 A limitation of applying this grading system to cytology specimens is that mitotic counts in cytology specimens are known to be unreliable. 53 In the current study, we found it difficult to assess mitoses in cytology specimens because mitoses were generally not preserved in aspirate smear slides, and in some cases low tumor cellularity limited our ability to provide accurate mitotic counts. For these reasons, mitotic count was not evaluated in the present study, and therefore it was not possible to perform formal 2021 WHO grading of E-DPM in cytology specimens.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although it is challenging to count mitosis in limited cytology materials, 22 alternative methods such as Ki-67 index have been explored but are extremely limited in the literature. 12,23,24 Thus, our current study aimed to (1) assess the correlation between Ki-67 index in EUS-FNA cytology blocks and mitotic count in follow-up surgical specimens, and (2) evaluate whether Ki-67 index can be used to predict mitotic rate and risk assessment preoperatively.…”
Section: Introductionmentioning
confidence: 99%